Analysis of the Implementation of a Problem-Based Learning (PBL)-Based IPAS E-Module on Elementary School Students’ Conceptual Understanding and Critical Thinking Skills - Meyrlin Santi Duppa; Solehun Solehun; Mursalim Mursalim (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to analyze the effect of implementing a Problem-Based Learning (PBL)-based IPAS e-module on elementary school students’ conceptual understanding and critical thinking skills. The problem underlying this study is the low level of students’ conceptual understanding and critical thinking skills in IPAS learning. This study employed a quantitative approach with a quasi-experimental design, specifically a nonequivalent control group design. The research sample consisted of 31 students divided into a control class and an experimental class. The instruments used included a conceptual understanding test and a critical thinking skills questionnaire. The results showed a significant improvement in the experimental class compared to the control class. The average posttest score in the experimental class (31.47) was higher than that of the control class (23.44), with a gain of 10.94 in the experimental class and 2.88 in the control class. The hypothesis test results showed that the calculated t-value was greater than the t-table value, and the significance value was less than 0.05, indicating a significant difference between the two groups. The conclusion of this study is that the Problem-Based Learning (PBL)-based IPAS e-module is effective in improving students’ conceptual understanding and critical thinking skills. This study implies that the integration of learning technology and problem-based models can improve the quality of IPAS learning in elementary schools and support the development of 21st-century skills.